Application of Headspace Solid-Phase Microextraction and Gas Chromatography-Mass Spectrometry in the Study of Volatile Chemicals from Solanum viarum Dunal - DIONGUE, ALIOU; LAI, PO-YUNG; LIN, CHIEH (Asian Journal of Chemistry, 2010)
Headspace solid-phase microextraction (HS-SPME) and gas chromatography with ion trap mass spectrometric detection were used to investigate the volatile chemicals profile from Solanum viarum, a perennial Solanaceae plant reported to have attracted and stimulated oviposition of Helicoverpa armigera, which is one of the most economically-damaging pests in tropical and subtropical regions. SPME fibers coated with 100 μm polydimethylsiloxane (PDMS) and 75 μm Carboxen (CAR)-PDMS were tested. The latter was chosen for optimizing extraction procedures. Differences in volatile chemicals composition were observed in several compounds, depending on the coating characteristics of the fiber used. The partition coefficient, K1, between the headspace phase and SPME polymeric coating, the relative standard deviation and the concentrations of the volatile chemicals from the leaves of S. viarum were investigated. The SPME method showed efficiency in extracting low molecular weight compounds from the leaves of S. viarum.